THU0175 T cell reactivity to β2 glycoprotein I in systemic lupus erythematosus and anti-phospholipid syndrome: Correlation with subclinical atherosclerosis. (23rd January 2014) - Spinelli, F.R.; Alessandri, C.; Marocchi, E.; Ceccarelli, F.; Capozzi, A.; Sorice, M.; Arca, M.; Pacelli, M.; Buttari, B.; Riganò, R.; Profumo, E.; Valesini, G.; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) and anti-phospholipid syndrome (APS) patients present a high prevalence of atherosclerosis associated with both traditional and disease-related risk factors. β2 glycoprotein I (β2GPI), the main antigen in APS, seems to represent a link between autoimmunity and endothelial dysfunction which is the earliest atherosclerotic lesion. Recently, β2GPI reactive T cells have been identified; however, their role in the atherosclerosis is still unknown. Objectives: Aim of this study was to evaluate early atherosclerosis in SLE and APS patients, correlate subclinical atherosclerosis with traditional and disease-related risk factors and investigate T cell reactivity to β2GPI and its relationship with the atherosclerotic process. Methods: We enrolled 50 SLE and 18 primary APS patients and 25 controls. Demographic and clinical data, including traditional cardiovascular risk factors, were recorded. Blood samples were collected to investigate autoantibodies and lipid profile. Monocyte β2GPI and Tissue Factor (TF) expression and peripheral blood mononuclear cells (PBMCs) proliferation after β2GPI stimulation were evaluated. Brachial artery Doppler ultrasound for flow-mediated dilation (FMD) and carotid arteries ultrasound for intima-media thickness (IMT) were performed. Results: We detected an increase in mean IMT (mIMT) (0.69 mm ± 0.12) and a decrease in FMD% (6.5±6.6) in SLE patients versus controls (p<0.05 and p=0.0001, respectively) and a decrease in FMD% in APS patients (13.4±12.3) versus controls (p<0.05). Univariate analysis demonstrated a correlation between atherosclerotic lesions and traditional and disease related risk factors; multivariate analysis confirmed as independent risk factors only total cholesterol levels, SLICC and steroid dose for SLE, anti-β2GPI and age for APS. Monocyte β2GPI and TF expression was higher in SLE (34.2±18.9 and 69.5±20.6) and APS (36.3±22.7 and 66.9±26.9) than in controls (18.6±13.7 and 18.6±13.7) (p=0.006 and p=0.001, respectively); no correlation between monocyte β2GPI and TF and IMT or FMD% was detected. β2GPI induced PBMC proliferation in 32% of SLE patients, 25% of APS patients and none in the controls. Proliferative response to β2GPI correlated with history of arterial thrombosis, thrombocytopenia and IMT >0.9 mm. Conclusions: β2GPI T cell reactivity and its correlation with IMT and arterial thrombosis suggest a role for β2GPI response in the pathogenesis of accelerated atherosclerosis described in SLE and APS patients. Our study shows a subclinical atherosclerosis in SLE and APS patients associated with traditional and disease-related risk factors. Disclosure of Interest: None Declared